Digital media literacy of rural communities after the COVID-19 pandemic - FX Sri Sadewo; Eufrasia Kartika Hanindraputri; Diyah Utami; Sugeng Harianto; Norida Canda Sakti; Ellen Emanuela; Febriandita Tedjomurti (Faculty of Social and Political Sciences, Universitas Diponegoro, 2026)
In Indonesia, digital literacy has become a major concern since the COVID-19 pandemic. The COVID-19 pandemic has forced the use of social media to disseminate information to rural areas. On the other hand, various public service activities have been digitized. These two aspects can only be utilized if you have an adequate level of digital literacy. This study uses quantitative methods to examine digital literacy and its influencing factors in rural areas, with a focus on Bojonegoro Regency. First, the digital literacy levels in most rural communities have shifted from low to high. One of them is digital ethics. Collective experience forces rural communities in Bojonegoro Regency to be cautious. Moreover, through SmartPLS calculations, the distance between residence and the district capital affects the level of digital literacy. The farther from the district capital, the lower the digital literacy. On the other hand, social capital factors, especially social participation, are highly beneficial for improving digital literacy.